The subject-object imperative: women and the colonial struggle in three West African novels (1998)
This paper examines the subjecet versus object mode of relationship in articulating conclusions and generalizations across gender bias in three culture-specific novels of West Africa. Two of the selected novels are written by women about women. The third, a sociological novel, is by a sympathetic male writer. Because two of the novels can be regarded as sociological works, a sociological model in literary criticism—Lucien Goldmann’s ‘Genetic Structuralism’— is adopted as the analytical methodology: Events and characters can be examined as subject or object. To reach a fair analysis, the roles must be reversed so that conclusions and judgments can be compared. By so doing, bias and prejudice will be revealed if conclusions have been unfair. This will therefore make for a more realistic portraiture in art and help toward more objective development of literary criticism in the area of gender studies